Modelo Sectrabank para mitigar el fraude informático en operaciones electrónicas a través de aplicaciones bancarias en dispositivos Android - Mayhuasca, Jorge (2024)
Cybercrime is a global problem that affects various sectors, particularly the financial sector, where cybercriminals exploit users' lack of security awareness to obtain confidential information through techniques such as phishing, smishing, vishing, and ultimately seizing the OTP code to carry out fraudulent transactions. The objective of this research is to develop the SectraBank model, which incorporates security measures such as the use of the IMEI code, fingerprint authentication, and geolocation to mitigate cyber fraud attacks, specifically in the forms of SIM Swapping and Fake Apps used by cybercriminals to capture the OTP code. To evaluate the effectiveness of the model, simulations of real attacks were conducted on mobile phones of 50 users, divided into control and experimental groups. The results demonstrated that SectraBank mitigated 98% of SIM Swapping attacks and 88% of Fake App attacks. Additionally, 98% of participants expressed their willingness to adopt the model. These results are crucial for the banking sector, as the proposed model offers a robust security strategy that could significantly reduce cyber fraud, enhancing both security and trust in mobile banking applications.